2020
DOI: 10.7150/ijbs.39919
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Human C4.4A Reveal the Unique Association of Ly6/uPAR/α-neurotoxin Domain

Abstract: Ly6/uPAR/α-neurotoxin domain (LU-domain) is characterized by the presence of 4-5 disulfide bonds and three flexible loops that extend from a core stacked by several conversed disulfide bonds (thus also named three-fingered protein domain). This highly structurally stable protein domain is typically a protein-binder at extracellular space. Most LU proteins contain only single LU-domain as represented by Ly6 proteins in immunology and α-neurotoxins in snake venom. For Ly6 proteins, many are expressed in specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…Most TFPD proteins contain a single TFPD, while LYPD3 and uPAR have two and three TFPDs, respectively [27,33]. TEX101 also has two TFPDs, as revealed in the current study.…”
Section: Comparison Of Tex101 With Other Tfpd Proteinssupporting
confidence: 76%
See 4 more Smart Citations
“…Most TFPD proteins contain a single TFPD, while LYPD3 and uPAR have two and three TFPDs, respectively [27,33]. TEX101 also has two TFPDs, as revealed in the current study.…”
Section: Comparison Of Tex101 With Other Tfpd Proteinssupporting
confidence: 76%
“…sequence identity 22%; Fig. S2A) [27]. We found that TEX101 indeed contained two LU domains (LU1 and LU2), both with a three-fingered protein domain (TFPD) fold (Fig.…”
Section: ; Figs 1 2 and S1)mentioning
confidence: 86%
See 3 more Smart Citations